2009
DOI: 10.1108/09596110910948323
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and extrinsic factors impacting casino hotel chefs' job satisfaction

Abstract: PurposeThe purpose of this paper is to explore intrinsic and extrinsic factors impacting the job satisfaction of casino hotel chefs, and whether chefs' background characteristics are associated with their overall and specific facets of job satisfaction.Design/methodology/approachA total of 152 surveys were analyzed using a randomly selected sample of 25 major casinos in Las Vegas, Nevada. The sample selection represented chefs working in various types of foodservice operations within the hotel segments.Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 31 publications
6
49
0
Order By: Relevance
“…This finding is similar to previous research which shows that the majority of top managerial positions are filled by men (Hertzman & Maas, 2012;Zopiatis, 2010;Kang et al, 2010;Chuang et al, 2009;Wang et al, 2011;Agut et al, 2003). There is also a higher representation of female chefs in certain sectors than others, with representation among the elite Michelin starred dining establishment even more marginal (Balazs, 2002;Druckman, 2010;Ko, 2012;Day, 2015).…”
Section: Gendersupporting
confidence: 80%
See 2 more Smart Citations
“…This finding is similar to previous research which shows that the majority of top managerial positions are filled by men (Hertzman & Maas, 2012;Zopiatis, 2010;Kang et al, 2010;Chuang et al, 2009;Wang et al, 2011;Agut et al, 2003). There is also a higher representation of female chefs in certain sectors than others, with representation among the elite Michelin starred dining establishment even more marginal (Balazs, 2002;Druckman, 2010;Ko, 2012;Day, 2015).…”
Section: Gendersupporting
confidence: 80%
“…These figures show that very high proportions of staff at managerial level are married, however this may also have some interaction with the age of managers as by the age of 40 years many who are going to marry will have done so. The one exception to these figures was from the study by Chuang et al (2009) among supervisors in LA casino hotels where only 52.7% of these employees were married with 42.8% being single. This finding, however, may have more to do with the culture of Los Angeles and its casinos.…”
Section: Marital Statusmentioning
confidence: 77%
See 1 more Smart Citation
“…Investigating job satisfaction and turnover intention, Karatepe et al (2006) found a negative association between the two constructs, while in their study of head chefs of casino hotels, Chuang, Yin, and Dellman-Jenkins (2008) investigated the extrinsic and intrinsic factors of job satisfaction. Furthermore, the aforementioned scholars found that the nature of the work was a major contributor to the chefs' job satisfaction, while recognition was a source of low satisfaction, and elements such as paid vacations, salary and sick leave were sources of dissatisfaction.…”
Section: Job Satisfaction and Labor Turnovermentioning
confidence: 99%
“…However, positive extrinsic regulated factors included good relationships with supervisors and co-workers, informal dress, decision-making participation, and international company culture, all of which positively affect employees' perceptions of career satisfaction (Ryan & Deci, 2000). In terms of extrinsic rewarded and regulated facets in the hospitality industry, again the study by Chuang et al (2009) on extrinsic regulated factors affecting casino hotel chefs' job satisfaction found that the chefs were happy with their supervision style but not at all with the company policy, specifically sick leave days and paid-holiday policies.…”
Section: Extrinsic Motivational Factors and Career Decisionsmentioning
confidence: 99%